One Health Education for Future Physicians: A Case Report of Cat-Transmitted Sporotrichosis. (12th February 2020) - Kaadan, M Ihsan; Dennis, Michael; Desai, Nancy; Yadavalli, Gopal; Lederer, Philip
Abstract: A healthy 35-year-old Brazilian woman presented with persistent redness, swelling, and multiple wounds on the hand 2 weeks after a cat bite in her home country. She was treated twice with amoxicillin-clavulanate but failed to demonstrate improvement. She then presented to our institution with a newly developed abscess on the right hand. Incision and drainage were performed and she was admitted to the hospital. She was subsequently treated with broad-spectrum antibiotics. Her symptoms improved but did not resolve. Four days after hospital discharge, a wound culture resulted as positive for Sporothrix schenchii . The patient was treated with itraconazole. Sporotrichosis is endemic in many countries including Brazil and is known to be transmitted by cat bites. Sporotrichosis should be considered in the differential diagnosis for patients who have symptoms of cellulitis after cat bites in an endemic area.